Vibration Response of Small-caliber Vehicular Gun Tube with Gear Backlash - Fan Chunlin; Qiu Xiaobo; Shan Dongsheng; Wang Yang (Jixie chuandong)
Aiming at the study the vibration response frequency and its displacement of small-caliber vehicular gun tube,the simplified model of elevating mechanism including gear backlash is established and the method of parameter identification of contact-impact mechanical model is given.Through the dynamics simulation by applying sinusoidal signal in ADAMS,the vibration response frequency of tube with backlash are compared with no backlash,and its displacement and velocity are obtained.The results show that the continuous multi-frequency phenomenon occurred with large range,which has a bad effect on projectile initial conditions and reduces firing accuracy.Based on this,the theoretical guidance in structure optimization of gun control and firing accuracy improvement is provided.